Pengaruh Media Sosial Terhadap Perkembangan Identitas Sosial Pada Siswa SMP 27 Maluku Tengah - Rehalat, Aminah; Nurul 'Ainy, Zuhria (Universitas Hamzanwadi, 2025)
Social media has become an important part of adolescents' lives, including in the formation of their social identity. This study aims to analyze the influence of social media on the development of social identity of students at SMP 27 Central Maluku. Using a quantitative method with a survey approach, data were collected through questionnaires given to 150 students selected by purposive sampling. Data analysis was carried out using descriptive statistics and simple linear regression. The results showed that social media has a significant influence on students' social identity, both in positive and negative aspects. Students use social media to express themselves, build communities, and broaden their horizons. However, social pressure, self-comparison, and the phenomenon of